2022
DOI: 10.1021/acs.langmuir.2c01208
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Coordination Polymer-Based Catalyst and Its Application in the Nitroaromatic Hydrogenation under Mild Conditions

Abstract: Nitroarene reduction has played a crucial role in the environment remediation and public health. However, few research studies have been undertaken regarding the use of infinite coordination polymer-based catalysts in this process. Herein, we are looking for a way to catalyze the reduction of nitroarenes using a new and well-designed coordination polymer-based palladium catalyst. The Co-BDC-NH 2 coordination polymer was prepared through a co-precipitation reaction between 2-amino-1,4-benzenedicarboxylic acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…Although this peak is covered by the bending vibration of the O−H and only a shoulder can be seen, it is the characteristic band of the imine group. 12,31,42 Eventually, in the FT-IR spectrum of LPMo-Cu (Figure 3d), all of the characteristic peaks of previous steps are seen, in addition to the shift of the imine peak to a lower frequency (1625 cm −1 ) as a result of the coordination of nitrogen to the Cu center. 43 X-ray diffraction (XRD) analysis was used as a qualitative analysis to identify the crystal structure of the prepared catalyst.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Although this peak is covered by the bending vibration of the O−H and only a shoulder can be seen, it is the characteristic band of the imine group. 12,31,42 Eventually, in the FT-IR spectrum of LPMo-Cu (Figure 3d), all of the characteristic peaks of previous steps are seen, in addition to the shift of the imine peak to a lower frequency (1625 cm −1 ) as a result of the coordination of nitrogen to the Cu center. 43 X-ray diffraction (XRD) analysis was used as a qualitative analysis to identify the crystal structure of the prepared catalyst.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The catalytic reduction of nitroaromatics to the corresponding aromatic amines is one of the most important reactions, as aromatic amines are essential organic intermediates for a variety of high-value chemicals such as perfumes, plastics, pharmaceuticals, and pesticides. Recently, it has been reported that the reduction of nitroaromatics can be facilitated at room temperature in the presence of NaBH 4 . , Nowadays, catalysts based on noble metals (Ru, Pd, Ag, Pt, Au, etc.) are widely utilized for the reduction of nitroaromatics due to their high catalytic activity .…”
Section: Introductionmentioning
confidence: 99%
“…All reports on compounds based on cyamelurates suggested good chemical stability in aqueous media, supporting their use in different catalytic processes under this condition. There have been many works that reported that CPs can be superior heterogeneous catalysts by different reactions. In this way, this work evaluated for the first time the use of a CP based on the tris- s -triazine derivative, iron­(III) cyamelurate, as a potential catalyst to boost the heterogeneous Fenton-like reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersion of g-C 3 N 4 in alkaline medium before and after refluxing, elemental composition and potentiometric titration curves, thermal gravimetric analysis, digital images, iron(III)-cyamelurate coordination polymer and suspension of the solid containing Fe 3+ ions in the presence of SCN − ions, degradation kinetics under different pH values in the presence of iron(III)-doped polymeric g-C 3 N 4 , pseudo-first-order kinetic rate for catalytic degradation, TON and TOF, comparison of the efficiencies for the degradation of IC dye(20, 200, and 2000 mg/L), FTIR spectra obtained for the catalyst before and after the catalytic tests and impact of radical scavengers, 1,4-benzoquinone and tert-butanol, on the IC degradation (PDF)Langmuir pubs.acs.org/Langmuir Article T h i s c o n t e n t i s o n l y l i c e n s e d f o r c o n s u m…”
mentioning
confidence: 99%